Desenvolvimento de um método multirresíduos de agrotóxicos em águas de abastecimento do estado do Ceará usando LC-MS/MS- SPE - Menezes, Marília Gabriela Gomes de (2019)
Supplies water goes through specific procedures in water treatment plants, aiming to provide the population with good quality water, free of impurities. However, the treatment steps produce only partial removal of chemical compounds such as pesticides, sometimes not enough to set low concentrations in the supplies water. Consolidation Ordinance nº5 published by the Brazilian Ministry of Health in 2017 governs the monitoring of water quality, among the potability parameters are the maximum values ​​allowed for some pesticides. In the present work a method for the determination of 8 pesticides in water supply was developed and validated using Solid Phase Extraction (SPE) for sample preparation and Sequential Mass Spectrometry (LC-MS/MS) coupled Liquid Chromatography, with triple quadrupole analyzer for the detection of pesticides. The SPE technique developed here has a sample acidification pretreatment with formic acid (10%) to pH 4, using a sample volume of 100mL, using the Oasis HLB 500mg polymeric sorbent and eluting pesticides in 7 0.5 ml of the (1/1) MeOH/DCM solution. The elaborated chromatographic methods allowed the identification and quantification of the compounds in 22min and 10min, in the positive and negative ionization modes, respectively. After validation, the method was considered selective for all compounds, presenting good linearity with coefficients of determination greater than 0.99 and statistical treatments that confirm their respective linearities. Only 2,4-D did not show good linearity. The working ranges are in the range 0.01-1.5 µg/L. And the limits of quantification ranged from 0.01-0.3 µg/L. The accuracy in the repeatability item presented RDS values ​​ranging from 0.7-20.9% and the intermediate precision between 2-24%, values ​​below 30%, indicated limit for the concentration range worked. Accuracy was assessed by recovery, some pesticides showed higher recoveries than recommended (40-120%). Twenty-seven real samples of water supply from the state of Ceará were analyzed, the results showed 78% contamination, however the concentration levels found were below the limits established by the current legislation. The proposed method can be used in routine laboratory analysis and can be an excellent tool used in pesticide monitoring programs in waters intended for human consumption in the state of Ceará.